2023
DOI: 10.1039/d2ay02044k
|View full text |Cite
|
Sign up to set email alerts
|

A boronate-affinity magnetic molecularly imprinted polymer for luteolin recognition

Abstract: In this study, 3-carboxyphenylboronic acid (CP) functionalized amino-modified Fe3O4 (Fe3O4@NH2-CP, FNC) magnetic molecularly imprinted polymers (FNC@MIPs) were synthesized and applied to the rapid identification and selective separation of Luteolin (LTL)....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…A combination of these covalent-non-covalent synergistic forces could induce the formation of more imprinted cavities in polymers. Meanwhile, by comparing with other MIPs based on different monomers reported in previous literature (Table 3), this present study demonstrated excellent adsorption performance and recognition ability (Gao et al, 2016;Guo et al, 2021;Tong et al, 2021;Ding et al, 2023).…”
Section: Comparative Studysupporting
confidence: 61%
See 1 more Smart Citation
“…A combination of these covalent-non-covalent synergistic forces could induce the formation of more imprinted cavities in polymers. Meanwhile, by comparing with other MIPs based on different monomers reported in previous literature (Table 3), this present study demonstrated excellent adsorption performance and recognition ability (Gao et al, 2016;Guo et al, 2021;Tong et al, 2021;Ding et al, 2023).…”
Section: Comparative Studysupporting
confidence: 61%
“…This strategy relies on the covalent binding interaction between boronic acid ligands and cis-diol-containing compounds at relatively higher pH values, with the complexes being released through dissociation under acidic conditions (Li et al, 2018;Bie and Chen, 2021;Li and Dong, 2021;. Fortunately, LTL contains the structure of cis-diols, and several researches have demonstrated that boronate affinity-based MIP could provide a new approach for the extraction and purification of LTL from natural products (Jia et al, 2018;Ding et al, 2023;Liu et al, 2023). Liu et al (2021) and has constructed two adsorbents, containing hydrophilic boronate affinity high internal phase emulsions MIP and graphene oxide-based MIP, which could capture and separate LTL from complex samples with high selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al. [197] synthesized 3‐carboxyphenylboronic acid (CP)‐modified amino‐modified Fe 3 O 4 (Fe 3 O 4 @NH 2 ‐CP, FNC) magnetic MIPs (FNC@MIPs) and utilized them for the prompt recognition and selective isolation of Luteolin (LTL). The research team comprehensively assessed the performance of FNC@MIPs and observed that they exhibit uniform morphology, exceptional magnetic characteristics, rapid binding kinetics, high adsorption capacity, satisfactory selectivity, and sustained reusability.…”
Section: Application Of Magnetic Composite Nanomaterials In Herbal Pr...mentioning
confidence: 99%
“…MIPs are a class of tailor-made materials and artificial antibodies. 22 They exhibit excellent recognition ability towards target molecules through the formatted special three-dimensional (3D) cavities by mimicking the antigen–antibody interactions. 23,24 Compared to other SPE materials, MIPs demonstrate high selectivity, good thermo-chemical stability, excellent mechanical strength, low cost, and easy preparation.…”
Section: Introductionmentioning
confidence: 99%